2016
DOI: 10.1039/c6fo01043a
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lentinus edodes β-glucans ameliorates DSS-induced ulcerative colitis in mice via MAPK-Elk-1 and MAPK-PPARγ pathways

Abstract: To evaluate the anti-inflammatory effect of β-glucans from Lentinus edodes, and its molecular mechanism, the dextran sulfate sodium salt (DSS) induced colitis model of mice and the LPS-stimulated RAW264.7 cell inflammation model were used in this study. 40 ICR male mice were randomly divided into 4 groups: Control, DSS (DSS treated only), DSS + low-βGs (500 mg kg d) and DSS + high-βGs (1000 mg kg d). The body weight of the mice with Lentinus edodes β-glucan supplementation increased significantly compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…It is reported that Lentinus edodes β-glucans (500 and 1000 mg/kg) treatment can increase the body weight, improve DAI and modify p38MAPK and ERK1/2 in DSSinduced UC mice, and then phosphorylate PPARγ, which negatively regulates activation of NF-κB [124].…”
Section: Tonifying Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that Lentinus edodes β-glucans (500 and 1000 mg/kg) treatment can increase the body weight, improve DAI and modify p38MAPK and ERK1/2 in DSSinduced UC mice, and then phosphorylate PPARγ, which negatively regulates activation of NF-κB [124].…”
Section: Tonifying Medicinementioning
confidence: 99%
“…Attenuate the expression of proteins in the NF-κB [122] Oligonol DSS-induced colon tissue Decrease nuclear translocation of NF-κBp65 [123] Lentinus edodes β-glucans RAW264.7 cells Inhibit NF-κB activation [124] Mango extract CCD-18Co cells Reduce expression of NF-κB and pNF-κB protein [125] Astringent medicine Muscovite Iodoacetamide-induced colitis tissues…”
Section: Aom/dss-induced Colon Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive derivative of acrolein, cinnamaldehyde, is indeed known for its antiproliferative and pro-apoptotic effects, and is now considered as having anticancer properties consisting in modulating cell signaling pathways: for instance, it inhibits survival PI3K/Akt signaling in a number of CRC cells [28] and activates cytoprotective antioxidant response in human epithelial colon cells by inducing Nuclear Factor-Erythroid 2-Related Factor 2 (NRF2) [29]. Increased MDA tissue levels have been detected in inflamed colonic tissues induced in rodents [30][31][32][33], by the administration of dextran sodium sulfate (DSS) in mice, or trinitrobenzene sulfonic acid (TNBS) in rats. These two chemicals are commonly employed in inducing experimental colitis [34,35].…”
Section: Acroleinmentioning
confidence: 99%
“…Elk-1, after phosphorylation by ERK, binds to the SRE cis-acting element in the promoter region of c-fos and induces its transcription. Transcription factor Elk-1 is a part of the ternary complex which can be combined with serum effect factors (SRE) to regulate gene activity in order to reply to the serum and growth factors [16]. The activation of ERKl/2 is transferred from the cytoplasmic to nuclear and activates its downstream substrate EIk-1, and the phosphorylation of EIk-1 will promote the function of cell differentiation, proliferation and apoptosis [17][18][19].…”
Section: Discussionmentioning
confidence: 99%